Selection of HIV-1 for resistance to fifth-generation protease inhibitors reveals two independent pathways to high-level resistance - Ean Spielvogel; Sook-Kyung Lee; Shuntai Zhou; Gordon J Lockbaum; Mina Henes; Amy Sondgeroth; Klajdi Kosovrasti; Ellen A Nalivaika; Akbar Ali; Nese Kurt Yilmaz; Celia A Schiffer; Ronald Swanstrom (eLife, 2023)
Darunavir (DRV) is exceptional among potent HIV-1 protease inhibitors (PIs) in high drug concentrations that are achieved in vivo. Little is known about the de novo resistance pathway for DRV. We selected for resistance to high drug concentrations against 10 PIs and their structural precursor DRV. Mutations accumulated through two pathways (anchored by protease mutations I50V or I84V). Small changes in the inhibitor P1'-equivalent position led to preferential use of one pathway over the other. Changes in the inhibitor P2'-equivalent position determined differences in potency that were retained in the resistant viruses and that impacted the selected mutations. Viral variants from the two pathways showed differential selection of compensatory mutations in Gag cleavage sites. These results reveal the high level of selective pressure that is attainable with fifth-generation PIs and how features of the inhibitor affect both the resistance pathway and the residual potency in the face of resistance.